Development of CALP through ICT and Lexical Approach in Second Generation Foreign Students (European Journal of Multidisciplinary Studies, 2017)
The public Italian School is a multicultural school: 51 percent of foreign students were born in Italy or arrived before starting primary school and their academic performance is lower than average, as verified by the Ministry of Education (MIUR 2015) and confirmed by a research group of Genoa University that assessed pupils’ prior knowledge in an elementary school. Consequently two research questions have been formulated:;1. A second generation foreign student has the same CALP (Cognitive Academic Language Proficiency, Cummins 1979) as an Italian student? 2. Can the development of CALP both in Italian and Spanish give significant results? If so, which ones? The project LI.LO (acronym of Lingua Italiana, Lingua di Origine) aims to study relations between heritage language and second language acquisition in CALP. It also has the purpose to build bilingualism programs in the public middle school by using ICT (Information and Communication Technologies) in order to improve academic proficiency and study skills in both languages. This paper wants to show the two basic phases of the project: in the first phase the researchers collected data about students’ linguistic prior knowledges and skills, showing a better competence in the section of the pre-test related to the lexicon. The analysis of the first phase was used to consider aims and guidelines for the bilingual course LI.LO. The method has been the Lexical Approach (Lewis, 1993, 1997) . Secondly the researchers opened the course on a platform CLAT/Clire, in which they put materials in both languages. ICT were used in many activities. In the contribute it will be shown analysis, results and further perspectives of the project.